WEBSITE INSTANSI KANTOR REGIONAL I BADAN KEPEGAWAIAN NEGARA YOGYAKARTA - , ALFIAH TRISNA ASSWANDARI, Muhammad Fakhrurrifki, S.Kom., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The fist regional office of Yogyakarta State civil service agency is government institution non Indonesian Ministry which does some government tasks in civil service management sector. The Work load of the fist regional ofice of Yogyakarta State civil service agency are civil servants and pensioners in Centar Java and Yogyakarta district.The first regional office serves information management personnel by manual, using information media banner that is placed in the lobby of the office, a one-stop service and office libraries. Along with development of information systems technology so it is built an agency website of the fist regional office of Yogyakarta State civil service agency. The system can perform the processing of profile data, news, regulations, agenda, Gallery, contact, polling and admin. The system is built by using a programming language web-based PHP framework CodeIgniter, assisted with Javascript with jQuery framework, Apache Webserver and database MySQL for administration. This system is able to help the spread of information management staffing, staffing rules, able to print provides a form of consultation and providing visitors a poll of visitors. For the future, making this system is expected to further assist and facilitate the provision of information and consultancy services to the community.